ACCOUNTABILITY AND PERFORMANCE: EVIDENCE FROM LOCAL GOVERNMENT - Mesri Welhelmina Nisriani Manafe; Rusdi Akbar (Journal of Indonesian Economy and Business (JIEB), 2014)
Local government accountability attracts attention since the issuance of the Presidential Instruction Number 7 of 1999 on Accountability Reporting of the Performance of Government Institutions (Instruksi Presiden No. 7 Tahun 1999 tentang Laporan Kinerja Instansi Pemerintah). In practice, this accountability is not as was expected. One indication of the causal factor of the failure of the accountability implementation program is that it is considered as an obligation to describe and to justify the behavior of the accountability actors. The objective of this study is to empirically examine the correlation between the requirements of various types of accountability with negative perception of the work context and the work performance of the accountability actors. It contributes to the empirical evidence for the correlation among the various types of accountability obligation and the work performance based on the institutional theory with mixed method, which is a quantitative approach with PLS and a qualitative approach with thematic analysis. Its samples are 201 SKPD officers in the local government of Nusa Tenggara TimurProvince. The results of the study show that the conflict in the accountability requirement has significant impact on the work context with negative perception at different levels, but does not have any significant impact on the work performance of the accountability actors.